2016
DOI: 10.1111/vru.12459
|View full text |Cite
|
Sign up to set email alerts
|

COMPARISON BETWEEN THORACIC RADIOGRAPHIC FINDINGS AND POSTMORTEM DIAGNOSIS OF THORACIC DISEASES IN DYSPNEIC COMPANION RATS (RATTUS NORVEGICUS)

Abstract: Companion rats are often presented to veterinarians for respiratory difficulties. Dyspnea in rats is most commonly due to infectious pneumonia, and thoracic neoplasia can go undiagnosed ante mortem due to a mistaken interpretation of pneumonia. In domestic carnivores, pulmonary nodular patterns have been shown to correlate with lung neoplastic diseases and infectious diseases. The main objective of this retrospective case series study was to determine whether certain radiographic criteria could be correlated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…It is known that thoracic radiographs present limitations regarding the ability to differentiate between infection and neoplasia. 22 A previous study indicated that the presence of cranial mediastinal lesions on radiographs may be helpful to differentiate neoplastic from infectious disease in rats, although mediastinal lesions were often difficult to detect on radiographs in this study. 22 In case 6, a blood smear was obtained just prior to euthanasia, which would have resulted in antemortem diagnosis of lymphoid leukemia had the animal not been euthanized.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…It is known that thoracic radiographs present limitations regarding the ability to differentiate between infection and neoplasia. 22 A previous study indicated that the presence of cranial mediastinal lesions on radiographs may be helpful to differentiate neoplastic from infectious disease in rats, although mediastinal lesions were often difficult to detect on radiographs in this study. 22 In case 6, a blood smear was obtained just prior to euthanasia, which would have resulted in antemortem diagnosis of lymphoid leukemia had the animal not been euthanized.…”
Section: Discussionmentioning
confidence: 56%
“…5,21 In a study evaluating rat thoracic radiographs in comparison with the postmortem diagnosis, lymphoma represented 72% of the neoplastic group, with lesions most commonly located in the cranial medias-tinum. 22 In this study, the radiographic interpretation was challenging and there were some difficulties differentiating pulmonary changes, cardiac changes, and mediastinal changes on radiographs. Additionally, some of the cases had evidence of suspected mediastinal change, such as widening, but no distinct mass noted.…”
Section: Discussionmentioning
confidence: 98%
“…It has been shown to improve procedural efficiency whilst decreasing complications, increasing success, and reducing financial strain ( 53 ). In the medical treatment of pet rats, the main advantage of RATTUS is the possibility of evaluating the thoracic wall without anaesthesia (in contrast to TXR or CT) ( 43 ). Due to the size of the thoracic cavity and the use of a linear probe, the examination is relatively quick and easily conducted.…”
Section: Discussionmentioning
confidence: 99%